The Role of Training and Innovation to Improve the Performance of Culinary Sector MSMEs in the Digital Era - Landreas Utama Lie; Budi Eko Soetjipto (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the relationship of human resource management strategies to increase employee retention in the digital era in culinary sector MSMEs located in Jombang, East Java. This research uses a quantitative approach using a survey method on 30 MSME employees. The sampling process uses a census technique, the data analysis technique used in this study uses SPSS software. The regression analysis results show that digital training has a significant positive influence on MSME performance (regression coefficient = 0.549; p < 0.05), while innovation also has a significant positive relationship (regression coefficient = 0.325; p < 0.05). Simultaneously, these two variables are proven to make a major contribution to MSME performance. This study supports the theory that technology-integrated human resource management strategies can increase employee loyalty and engagement in MSMEs. The practical implication of this study is the need for MSMEs to adopt technology-based training and innovation in structured business management strategies to improve MSME performance. This research also contributes to the literature related to HR management strategies in the digital era, especially in the context of MSMEs.